PENGARUH PELATIHAN DAN PENEMPATAN TERHADAP KINERJA KARYAWAN DI PT VASAN MANDIRI INDONESIA - Yoga, Yoga Syahputra; Nora Pitri Nainggolan (LPPM Universitas Putera Batam, 2022)
Human resources are also one of the biggest supporters in the running of an activity that occurs within the company, although almost all companies use machines to carry out production, but companies still need human resources to run these machines, therefore human resources are the most important aspect in company. This will be an important issue for the company in providing training and placement of employees because it will have an impact on employee performance. The purpose of this study was to determine the partial and simultaneous influence between training and placement on employee performance. The technique used in this study is to identify the partial effect (t test) and simultaneous effect (f test) between the training variables (X1) and placement (X2) on employee performance (Y) at PT Vasan Mandiri Indonesia. The method used in this research is descriptive analysis using SPSS version 25 program tools. Data collection techniques were carried out by distributing questionnaires to employees of PT Vasan Mandiri Indonesia as many as 110 respondents. The results of the coefficient of determination (R2) in the summary model seen from the R square of the training, placement, and employee performance variables worth 0.673 or 63.7%, while the t-test on the training variable with a significance of 0.000 <0.05 and the placement variable with a significance 0.001 <0.05, each variable has a significant effect on employee performance variables. The results of the F test are 98,803> 2.69 and a significance value of 0.000 <0.05 which shows that the training and placement variables simultaneously have a significant effect on employee performance.